Recent technological advances in correlative light and electron microscopy for the comprehensive analysis of neural circuits - Iwasaki, Hirohide; Ichinose, Sotaro; Tajika, Yuki; Murakami, Tohru (Frontiers in Neuroanatomy, 2022)
Light microscopy (LM) covers a relatively wide area and is suitable for observing the entire neuronal network. However, resolution of LM is insufficient to identify synapses and determine whether neighboring neurons are connected via synapses. In contrast, the resolution of electron microscopy (EM) is sufficiently high to detect synapses and is useful for identifying neuronal connectivity; however, serial images cannot easily show the entire morphology of neurons, as EM covers a relatively narrow region. Thus, covering a large area requires a large dataset. Furthermore, the three-dimensional (3D) reconstruction of neurons by EM requires considerable time and effort, and the segmentation of neurons is laborious. Correlative light and electron microscopy (CLEM) is an approach for correlating images obtained via LM and EM. Because LM and EM are complementary in terms of compensating for their shortcomings, CLEM is a powerful technique for the comprehensive analysis of neural circuits. This review provides an overview of recent advances in CLEM tools and methods, particularly the fluorescent probes available for CLEM and near-infrared branding technique to match LM and EM images. We also discuss the challenges and limitations associated with contemporary CLEM technologies.